Educators as learners : creating a professional learning community in your school - Wald, Penelope Jo; Castleberry, Michael S., 1945- (Association for Supervision and Curriculum Development, 2000)
Explains how to change a school into a true "community of learners" in which teachers work together to keep themselves constantly learning and, thereby, help students learn; provides guidance, case studies, activities, and group-work tools